Perspectives: Evaluation of Older Adult Cochlear Implant Candidates for Fall Risk in a Developing Country Setting - Rogers, Christine (Frontiers in Neurology, 2021)
Dizziness, vertigo, and falls are common in older adults. Data suggest that cochlear implant candidates are no different and could be argued to be at elevated risk due to the presence of hearing loss and likely vestibular involvement. Perspectives contextualizes current testing and screening paradigms for vestibular deficits and fall risk and suggests a protocol suitable for use in developing country settings.